Misioneros y la cultura del escrito en el siglo XVI. Una mirada desde China - Romano, Antonella (2014)
The present article studies the role of the missionary in the transmission of knowledge between Europe and Asia, particularly China, in the sixteenth century. Thanks to educational institutions established by the Jesuits and other religious orders in various parts of the world, there was an exchange of texts between Europe and the Far East. The result was a first orientalism, with missionaries (Jesuit and otherwise) as its principal agents, which not only translated European texts to China, but also carried knowledge to Europe from the Ming Empire.